Resistance training improves quality of life in people with HIV: a randomized clinical trial - Hugo Zanetti; Camilo Lourenço; Lucas Cruz; Edmar Mendes (Revista Brasileira de Atividade Física e Saúde)
The study aimed to evaluate the effect of periodized resistance training on the quality of life of people infected with HIV. Thirty HIV-infected people, sedentary and receiving antiretroviral therapy, were randomly divided into two groups. The resistance training group (RT) participated in a 12-week periodized exercise program while the control group (CON) was asked to maintain daily habits. Before and after the twelve weeks, all volunteers answered a quality of life questionnaire (Patient-Reported Outcomes Quality of Life-HIV) in the Portuguese language version, containing eight domains: 1) physical health and symptoms (PHS); 2) body change (BC); 3) social relationships (SR); 4) intimate relationships (IR); 5) stigma (ST); 6) emotional distress (ED); 7) health concerns (HC); and 8) treatment impact (TI). A mixed-design analysis of variance for repeated measures was used to analyze the effects of time, treatment and interaction, having significant value when p <0.05. Interactions were found for the following domains: PHS (p <0.0001), BD (p <0.0001), SR (p <0.0001), IR (p<0.002), ST (p <0.0001), ED (p <0.0001), HC (P <0.0001) and TI (p <0.0001). RT improves quality of life in HIV-infected individuals and points to the need for its implementation in health care services targeted at this population.